The Impact of Farm Credit in Pakistan - Khandker, Shahidur R.; Faruqee, Rashidur R. (World Bank, Washington, DC, 2014)
Both formal, and informal loans matter in agriculture. But formal lenders provide much more in production lending, than do informal lenders, often at a higher cost than what they can recover. The Agricultural Development Bank of Pakistan (ADBP), for example, providing about 90 percent of formal loans in rural areas, incurs high costs on loan defaults. Like other governments, the Government of Pakistan subsidized the formal scheme on the grounds that lending to agriculture is a high-risk activity, because of covariate risk. Because farm credit schemes are subsidized, policymakers must know if these schemes are worth supporting. Using recent data from a large household survey from rural Pakistan, the authors estimate the cost-effectiveness of the ADBP loans. To estimate credit's impact, they use a two-stage method, which takes into account the endogeneity of borrowing. Clearly, formal lenders are biased toward larger farmers with collateral. Large landowners, who tend to represent only four percent of rural households, get 42 percent of formal loans. Landless, and subsistence farmers, who represent more than 69 percent of rural households, receive only 23 percent of formal loans. ADBP loans improve household welfare but, although large farmers receive most of ADBP finance, the impact of credit is greater for small farmers than for large farmers. Large landowners use formal loans unproductively. Because the ADBP scheme is subsidized, it is not cost-effective for delivering rural credit. It would be more cost-effective is small farmers were better targeted instead.